Three New Species of Opistholeptus Bergroth from West Africa (Heteroptera: Lygaeidae). - Slater, James Alexander (Contributions to Entomology = Beiträge zur Entomologie, 1953)
Nomenclatural Actschinai Slater, 1953 (Opistholeptus), spec. n.jordani Slater, 1953 (Opistholeptus), spec. n.parvus Slater, 1953 (Opistholeptus), spec. n.